CHROMOPHORIC DISSOLVED ORGANIC MATTER (CDOM) DAN NUTRIEN TERLARUT DI SUMBER AIR DI BALI UTARA - Suryaputra, I Gusti Ngurah Agung (Universitas Pendidikan Ganesha, 2023)
The objective of this study was to determine the absorbance of chromophoric dissolved organic matter (CDOM) and dissolved nutrient concentration in a spring water located at Sanggalangit, Kecamatan Gerokgak, Kabupaten Buleleng in North Bali, and to analyze the effect of rainfall on the water. The subjects in this study were filtered spring water using 0.7 µm GF/F filter paper. The object of this research were CDOM absorbance and dissolved nutrients concentration. Absorbance and dissolved nutrients concentration was measured using UV-Vis spectrophotometer. The absorbance was then used to calculate S275-295, S350-400, and E2:E3. Results show that S275-295 and S350-400 have a negative trend with rainfall. Rainfall affects E2:E3 but does not influence dissolved nutrients concentration (nitrate, nitrite, ammonia, and phosphate) and pH parameters both in environmental conditions when it is raining or hot. According to the regulation, the quality of spring water is categorized good, chemically.